Quand vieillir ensemble fait mal : les mauvais traitements entre conjoints âgés - Gravel, Sylvie; Beaulieu, Marie; Lithwick, Maxine (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1997)
This article focuses on a rarely discussed and relatively unknown type of elder abuse: elder abuse by a spouse. The data presented comes from a study examining the dynamics of elder abuse cases in three CISC's in Quebec (Local Centre for Community Services). Firstly, the characteristics associated with forms of abuse and both the abused spouse and the abusive spouse are described. Cases of elder abuse by a spouse are also compared with the other cases of elder abuse in the sample: abuse by a child, another family member, a friend or an acquaintance. Secondly, the authors examine more specifics situations of elder abuse by a spouse such as situations where one of the spouses has cognitive impairment and how that differs from situations where both spouses are lucid. For each of these situations, the different elements having an impact on the dynamics of abuse are discussed.